2007
DOI: 10.1590/s0102-05362007000400013
|View full text |Cite
|
Sign up to set email alerts
|

The use of sunn hemp as green manure intercropped with taro

Abstract: An experiment was carried out in Magé, Rio de Janeiro State, Brazil, to evaluate the performance of taro (Colocasia esculenta) intercropped with sunn hemp (Crotalaria juncea), used as green manure. A randomized blocks design with four replicates was used and the soil of the field plots was classified as Haplic Gleysol. Treatments consisted of taro (1) intercropped with unpruned sunn hemp, (2) intercropped with sunn hemp cut at soil level, (3) intercropped with sunn hemp pruned at its mid-height, and (4) in mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 1 publication
1
11
1
1
Order By: Relevance
“…The result revealed that growth parameters (Table 1) In line with the above findings superior performance of sole crop in terms of plant height, plant canopy, petiole diameter, number of leaves per plant and leaf area was also revealed in the experiments of Oliveira et al, (2007), Chattopadhyay et al, (2008), Osundare and Agboola (2003) and Thirumdasu et al, (2015), respectively. Fresh and dry weigh of plants are important traits, as they are directly related to the dry matter and food reserve accumulation in plants.…”
Section: Resultssupporting
confidence: 72%
“…The result revealed that growth parameters (Table 1) In line with the above findings superior performance of sole crop in terms of plant height, plant canopy, petiole diameter, number of leaves per plant and leaf area was also revealed in the experiments of Oliveira et al, (2007), Chattopadhyay et al, (2008), Osundare and Agboola (2003) and Thirumdasu et al, (2015), respectively. Fresh and dry weigh of plants are important traits, as they are directly related to the dry matter and food reserve accumulation in plants.…”
Section: Resultssupporting
confidence: 72%
“…Sunn hemp has been used in several tropical cropping systems for control of several nematode species and weeds (Valenzuela and Smith, 2002;Wang et al, 2002Wang et al, , 2008, including a taro intercropping system (Oliveira et al, 2007). An additional benefit from sunn hemp is that it is a legume and can fix atmospheric N 2 , making it a sustainable alternative to synthetic N fertilizer inputs.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Oliveira et al (2004) focused on the involvement of the taro consortium with sunn hemp and demonstrated its ability to produce significant amounts of N in the plant biomass. The taro and sunn hemp consortium also promotes nutrient cycling and shows a large increase in the organic matter due to the high dry matter content after pruning (Silva et al, 2006;Oliveira et al, 2007). This does not compromise the productivity of the commercial rhizomes produced by taro (Oliveira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The taro and sunn hemp consortium also promotes nutrient cycling and shows a large increase in the organic matter due to the high dry matter content after pruning (Silva et al, 2006;Oliveira et al, 2007). This does not compromise the productivity of the commercial rhizomes produced by taro (Oliveira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%